The vampire diaries. The complete fifth season - Anderson, Lance; Butler, Joshua, 1973-; Dobrev, Nina, 1989-; Wesley, Paul, 1982-; Somerhalder, Ian, 1978-; Smith, L. J., (Lisa J.) (Burbank, CA : Warner Bros. Entertainment, 2014)
Two vampire brothers, one good and one evil, move to a small town and try to win the heart of one of the teenage girls.
I know what you did last summer -- True lies -- Original sin -- For whom the bell tolls -- Monster's ball -- Handle with care -- Death and the maiden -- Dead man on campus -- The cell -- Fifty shades of Grayson -- 500 years of solitude -- The Devil inside -- Total eclipse of the heart -- No exit -- Gone girl -- While you were sleeping -- Rescue me -- Resident evil -- Man on fire -- What lies beneath -- Promised land -- Home.
Based on the series by L.J. Smith.
DTS-HD Master Audio 5.1, anamorphic wide screen 1.78:1.
Features: featurettes, gag reel, deleted scenes, UltraViolet enabled digital copy.
Nina Dobrev, Paul Wesley, Ian Somerhalder, Steven R. McQueen, Candice Accola.
Originally broadcast on television 2013-2014.
TV rating: Not rated.
Keywords: Vampires -- Drama; Brothers -- Drama; Triangles (Interpersonal relations) -- Drama; Vampire television programs; Television series; Fiction television programs; Video recordings for the hearing impaired; Fantasy television programs; Horror television programs